2011
DOI: 10.1029/2010wr009884
|View full text |Cite
|
Sign up to set email alerts
|

Localized bedrock aquifer distribution explains discharge from a headwater catchment

Abstract: [1] Understanding a discharge hydrograph is one of the leading interests in catchment hydrology. Recent research has provided credible information on the importance of bedrock groundwater on discharge hydrographs from headwater catchments. However, intensive monitoring of bedrock groundwater is rare in mountains with steep topography. Hence, how bedrock groundwater controls discharge from a steep headwater catchment is in dispute. In this study, we conducted long-term hydrological observations using densely lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…Okazaki et al (2013) suggested incorporating a hydrograph separation scheme of Hino and Hasebe (1984) with the storage estimation scheme by Kirchner (2009). The methodological effectiveness would be supported by the field-based study by Kosugi et al (2011) who demonstrated how different aquifers within a watershed contribute to the form of hydrograph at the watershed outlet. Okazaki et al (2013) succeeded in estimating a better hourly storage change than the original method by Kirchner (2009), however they did not describe their scientific contribution nor the further potential for applications well.…”
Section: Introductionmentioning
confidence: 79%
“…Okazaki et al (2013) suggested incorporating a hydrograph separation scheme of Hino and Hasebe (1984) with the storage estimation scheme by Kirchner (2009). The methodological effectiveness would be supported by the field-based study by Kosugi et al (2011) who demonstrated how different aquifers within a watershed contribute to the form of hydrograph at the watershed outlet. Okazaki et al (2013) succeeded in estimating a better hourly storage change than the original method by Kirchner (2009), however they did not describe their scientific contribution nor the further potential for applications well.…”
Section: Introductionmentioning
confidence: 79%
“…Although piezometers can give significant, yet local, insights on the groundwater system (Kosugi et al 2011;Padilla et al 2014), their cost, their short lifespans in unstable areas and their poor representativeness make piezometers seldom used in landslide studies (Michoud et al 2013). Consequently, recent studies focus on indirect methods such as hydrochemistry surveys by monitoring springs for natural and artificial tracers (Bogaard et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Winter et al (2008) and Tiedeman et al (1998) monitored 31 bedrock wells and found water table gradients caused by different geological units within a catchment. Even in headwater catchments, variability in groundwater dynamics has been found due to multiple underlying aquifers (Kosugi et al, 2008(Kosugi et al, , 2011. In Plynlimon catchment in Wales, Haria and Shand (2004) found that groundwater at 1.5, 10 and 30 m depth was not hydraulically connected, and was chemically stratified, with distinct pH, electrical conductivity and redox characteristics.…”
Section: Groundwater Variabilitymentioning
confidence: 99%